2011
DOI: 10.1371/journal.pntd.0001147
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Dengue Fatal Cases Diagnosis: NS1 Antigen Capture in Tissues

Abstract: Abstract/Background Dengue is the most important arthropod borne viral disease worldwide in terms of morbidity and mortality and is caused by any of the four serotypes of dengue virus (DENV-1 to 4). Brazil is responsible for approximately 80% of dengue cases in the Americas, and since the introduction of dengue in 1986, a total of 5,944,270 cases have been reported including 21,596 dengue hemorrhagic fever and 874 fatal cases. DENV can infect many cell types and cause diverse clinical and pathological effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
3
17
0
1
Order By: Relevance
“…NS1 detection thus offers a larger window of opportunity for diagnosis of dengue compared with virus isolation, RT-PCR or NASBA [68,72]. Commercially available NS1 capture-based detection kits with sensitivities that ranged from 54.2 to 93.4% have been comprehensively evaluated ( Anti-NS1 antibodies can also be used to detect infection in other sample sources, such as tissues, including liver, lung and kidney [104], through immunohistochemistry. This could be useful in postmortem studies.…”
Section: Antigen Detectionmentioning
confidence: 99%
“…NS1 detection thus offers a larger window of opportunity for diagnosis of dengue compared with virus isolation, RT-PCR or NASBA [68,72]. Commercially available NS1 capture-based detection kits with sensitivities that ranged from 54.2 to 93.4% have been comprehensively evaluated ( Anti-NS1 antibodies can also be used to detect infection in other sample sources, such as tissues, including liver, lung and kidney [104], through immunohistochemistry. This could be useful in postmortem studies.…”
Section: Antigen Detectionmentioning
confidence: 99%
“…21 Therefore, in this study, the NS1Ag test was critical despite the predominance of DENV-4 in 2012, which is difficult to detect with the NS1Ag test. 22 Virus isolation and RT-PCR had low detection sensitivities of 11.5% and 8.5%, respectively. Several factors may have contributed to this low sensitivity: viral isolation and RT-PCR would be less sensitive if death occurred after defervescence; the possibility of bacterial contamination; the lability of RNA, considering that it was isolated from postmortem material.…”
Section: Discussionmentioning
confidence: 98%
“…This study showed the importance of using all available techniques for dengue diagnosis in postmortem cases, as demonstrated in other studies. [22][23][24] The most common signs and symptoms were fever, respiratory distress, dyspnea, cough, vomiting, abdominal pain, headache, and prostration. Dengue is traditionally defined as an acute febrile illness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 33 ] Viral antigen detection is particularly useful during the first 5 days of illness with NS1 assays. [ 34 35 ]…”
Section: Discussionmentioning
confidence: 99%